Children's understanding of multiplication and division: Insights from a pooled analysis of seven studies conducted across 7 years. (14th November 2017) - Dubé, Adam K.; Robinson, Katherine M.
Abstract : Research suggests that children's conceptual understanding of multiplication and division is weak and that it remains poor well into the later elementary school years. Further, children's understanding of fundamental concepts such as inversion and associativity does not improve as they progress from grades 6 to 8. Instead, some children simply possess strong understanding while others do not. Other studies have identified an increase across these grades. The present investigation analyses data from seven studies of Grade 6 ( n = 226), Grade 7 ( n = 221), and Grade 8 ( n = 216) children's three‐term problem‐solving (e.g., 3 × 24 ÷ 24 and 3 × 24 ÷ 6) and provides a unified account of multiplication and division understanding, one in which grade differences and individual variability coexist and are moderated by sex. Statement of contribution What is already known on this subject? Children's conceptual understanding of multiplication and division is weak and it is unclear whether it increases across the key grades of 6–8. Understanding of the inversion and associativity concepts is characterized by high individual variability, but grade and sex have never been found to be a contributing factor. What does this study add? A meta‐analysis of seven data sets ( n = 643) indicates that grade differences and individual variability coexist and are moderated by sex. Understanding increases across grade only for boys, but an equal number of boys and girls are in the top 10% of conceptual problem‐solvers.